HUBUNGAN DISIPLIN DAN KEBIASAAN BELAJAR DENGAN HASIL BELAJAR MENGGAMBAR TEKNIK MAHASISWA JURUSAN SENI RUPA UNIVERSITAS NEGERI PADANG - REZKI DRES MILI, Dra. Zubaidah, M. Pd, Drs. Wisdiarman, M.Pd (Serupa The Journal of Art Education, 2014)
The Purpose of this research are analyze and explain about student’s achievement and to see how relation between variable of dicipline and variabel of study habit with student’s achievement. Kind of the research are descriptive and correlation. Tecnique sampling are done random population (Simple Random Sampling). Data of student’s achievement are took lecturer of draw tecnique subject, dicipline and study habit from angket with skala likert have try validity and reability. Then analyze of data us statistic metod for correlation analyze. Result of data analyze show such as: (1) Dicipline give correlation in the number of 0,411 to student’s achievement, (2) Study habit give correlation in the number of 0,432 to student’s achievement, (3) Dicipline and study habit give correlation the number of 0,495 to student’s achievement tecnique of drawing Visual Art Education in 2013/2014.Key words : Dicipline, Study Habit, Student’s Achievement, Tecniqueof Drawing